MICROSURGERY AND NERVE RECONSTRUCTION IN COMPLEX BRACHIAL PLEXUS INJURIES: PROGNOSIS AND LIMITATIONS - Guimarães Betini, Felipe; Carvalho Meneghetti, Matheus; Felipe dos Santos Silva, Ricardo; Pedro do Valle Varela, João; dos Santos Abreu, Roberta; da Silva Deascanio, Juliana; de Figueiredo Moutinho, Bruno; Clara Gama Pessanha, Maria; Guedes Saib Abi-Habib, Sayd; Resende Moreira, Raissa; von Krüger de Alcântara e Silva, Izabele; Isadora Miosso, Letícia; et al. (Health and Society, 2025)
Complex brachial plexus injuries represent a major challenge in medicine, as they can result in severe motor and sensory deficits, significantly impacting patients’ quality of life. Microsurgery and nerve reconstruction techniques have evolved to restore upper limb function, but they still have limitations in terms of full recovery of functionality. The prognosis varies according to the severity of the injury, the time elapsed before the intervention and the surgical approaches used. This study aims to analyze the advances in microsurgery in brachial plexus reconstruction, assessing the prognosis and limitations of these approaches in patients with complex injuries. This is a bibliographic review with qualitative premises, using the SciELO, PubMed and Google Scholar databases to search for scientific articles. To refine the search, the health descriptors “brachial plexus”, “microsurgery”, “nerve reconstruction” and “nerve transfers” were used, applying Boolean operators to optimize the results. The time frame covers the years 2019 to 2023, according to the date of the first and last reference selected. Advances in microsurgery have allowed for better functional recovery rates, especially with techniques such as nerve grafts, nerve transfers and neurotizations. Nerve transfers have stood out for reducing reinnervation time, favoring better motor results. However, factors such as the chronicity of the injury, surgical time and the patient’s neural plasticity significantly influence outcomes. Limitations include the need for prolonged rehabilitation, variability in functional results and difficulty in restoring fine movements and adequate muscle strength. It is concluded that microsurgery and nerve reconstruction are fundamental strategies in the rehabilitation of patients with complex brachial plexus injuries, providing partial or significant recovery of upper limb function. Despite advances, challenges such as prolonged recovery time and limitations in complete nerve regeneration still persist. New approaches, including regenerative therapies and tissue engineering, may contribute to better prognoses in the future.